Genetic variation analysis and kinship relationship between Dayak Ngaju tribe and Dayak Bukit tribe through examination of core DNA of Bukit CODIS STR Locus (combine DNA index system) 13 for the purpose of Forensic Identification - Iwan Aflanie1 , Wening Prastowo2 , Roselina Panghiyangani3 , Ahmad Yudianto4 , Toetik Koesbardiati5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dayak Ngaju tribe lived scattered along the Kapuas and Kahayan river. Meanwhile, the Dayak Bukit tribe lived scattered the mountain and valley area. Kinship between Dayak Bukit and Dayak Ngaju tribe is still under debate. DNA examination is one of the most reliable methods in determining personal identity, community, and kinship relationship. FBI has recommended DNA analysis using 13 short tandem repeat loci, known as CODIS 13 for DNA test. We used the system to identify the difference between Dayak Ngaju and Dayak Bukit tribe and analyze the kinship between these two tribes. There are loci and alleles that always owned by each individual of Dayak Ngaju tribe. The Dayak Ngaju characteristic which cannot be discovered in Dayak Bukit tribe are TPOX allele 6 locus, FGA allele 25.2 locus, CSF allele 8, 10.3, 11 locus, VWA allele 13, 15.1 locus, D18S51 allele 9, 13, 18, 20 locus, D21S11 allele 34 locus, D7S870 allele 12.1 locus. Dayak Bukit tribe has locus and allele that owned by each individual of Dayak Bukit tribe. The Dayak Bukit tribe characteristic which cannot be discovered in Dayak Ngaju tribe are FGA alleles 18.3, 19.3, 21.2, 23, 23.1 locus, CSF allele 28.2 locus, D7S870 allele 7.3 and allele 8 locus. The similarity of Dayak Ngaju tribe and Dayak Bukit tribe lied on 5 dominant loci named THO1 allele 9.3 locus, D5S818 allele 11, VWA allele 16, D3S1358 allele 16, D13S317 allele 8, but these loci are also found in Banjar Hulu tribe. The similarity that only discovered in Dayak Ngaju and Dayak Bukit tribe are located in TPOX allele 7 locus, FGA allele 20.2, 20.3, and D3S1358 allele 15.2. According to the research results above, it can conclude that Dayak Ngaju tribe doesn’t have a close kinship to the Dayak Bukit tribe.